نظام التربية الإسلامية في المملكة العربية السعودية - Fahad Mathar al-Syahrani (Universitas Islam Negeri (UIN), 2015)
This article contains a descriptive study about the education system in Saudi Arabia, which is based on Islamic teachings. This system maintains the universality and comprehensiveness of Islam education, which sets the foundation of all subsystems. Islamic education system in the Kingdom of Suadi Arabia (KSA) begins with developing and nurturing individuals, family and society. The system is designed to enhance Islamic education in order to prepare Muslim generations in facing future needs and challenges. It is therefore important to elucidate the philosophy, curriculum, and principles of Islamic education. Islamic education system in the Kingdom of Saudi Arabia has several characteristics, including divinity, unversal, rational, continuous, balance, and realistic.   DOI: 10.15408/tjems.v1i2.1273